2016
DOI: 10.1111/cch.12433
|View full text |Cite
|
Sign up to set email alerts
|

Talking with young children about concussions: an exploratory study

Abstract: Background Concussion education for children early in their participation in organized sport may help shape lasting attitudes about concussion safety. However, existing programming and research focus on older ages. Methods Qualitative interviews about concussions were conducted with twenty children between the ages of six and eight. Structural, descriptive and pattern coding were used to organize the transcribed interviews and identify emergent themes. Results Eighteen of the participants indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…Fifteen of the articles in this review discussed levels of concussion knowledge among children and youth who engage in sports (see Table 2 ). Two of the studies used qualitative designs ( Chrisman et al., 2013 ; Kroshus et al., 2017 ); the other 13 used quantitative methods—but notably, all studies used convenience sampling. Although findings varied, more of the studies found that children and youth had limited concussion knowledge or significant gaps in their knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen of the articles in this review discussed levels of concussion knowledge among children and youth who engage in sports (see Table 2 ). Two of the studies used qualitative designs ( Chrisman et al., 2013 ; Kroshus et al., 2017 ); the other 13 used quantitative methods—but notably, all studies used convenience sampling. Although findings varied, more of the studies found that children and youth had limited concussion knowledge or significant gaps in their knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies also examined factors that may be associated with level of concussion knowledge: age, gender, and history of concussion. Three studies found that athletes aged 14 years and older had significantly better scores on concussion knowledge than younger athletes (Cusimano et al, 2009;Kurowski et al, 2014;Mrazik et al, 2015) although Kroshus et al (2017) highlighted that some younger children had a reasonable knowledge of concussion. Among the three studies that examined gender differences, there were consistent findings that females showed higher levels of concussion knowledge than males (Kurowski et al, 2014;Myrdal et al, 2017;Wallace et al, 2017).…”
Section: Surveymentioning
confidence: 99%
“…The limited number of educational efforts tailored to athletes age 10 and under may be a contributing factor to these differences. An exploratory study by Kroshus, Gillard, Haarbauer-Krupa, Goldman, and Bickham (2016) identified knowledge gaps among young athletes and recommended the development of ageappropriate concussion education programming (Kroshus et al, 2016). Larger studies that assess the educational needs of the youngest athletes and their coaches, and an examination of age-appropriate concussion messages and educational materials is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…While there was some hesitancy among participants, the athletes in our study mostly agreed they had a responsibility to report concussion symptoms on behalf of a teammate and they would expect their teammates to do the same for them. Kroshus et al (2016) also examined the role of teammates and concussion reporting behaviors. In this study, authors found that athletes who felt their teammates held positive views on concussion safety were more likely to state they would encourage their teammates to report their concussion (Kroshus, Garnett, Baugh, & Calzo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This study explores a unique area of concussion research by focusing on opportunities to improve coach-athlete communication about concussion (Kroshus, Gillard, Haarbauer-Krupa, Goldman, & Bickham, 2016) and factors related to athletes' readiness to report concussion symptoms. The qualitative approach used allowed for in-depth discussions.…”
Section: Practical Implicationsmentioning
confidence: 99%